Executive Compensation and Regulation Imposed Governance: Evidence from the California Non-Profit Integrity Act (2004) - Dhole, Sandip (Institutional Knowledge at Singapore Management University, 2015)
This study examines the impact of the California Nonprofit Integrity Act of 2004 on CEO compensation costs in affected organizations. Contrary to the stated objective of the Act that executive compensation is “just and reasonable,” we find that CEO compensation costs for affected nonprofits during the post-regulation periods have increased by about 6.3 percent when compared with a control group of comparable unaffected nonprofits. In addition, the relative increase in CEO compensation appears to come from nonprofits that have experienced greater regulatory cost increases. We do not find evidence that the Act resulted in a change in CEO pay performance sensitivity. The observed CEO pay increase is not systematically different across nonprofits that underpaid versus those that overpaid their CEOs during pre-Act periods. Overall, this paper highlights the unintended consequences of regulatory attempts to enhance governance in the not-for-profit sector.